Imaging features of lacrimal gland disease - Caltabiano, Carmelo; Rana, Khizar; Buckby, Alexander; Patel, Sandy; Selva, Dinesh (Frontiers in Ophthalmology, 2026)
Lacrimal gland masses represent a diverse group of pathological processes, including inflammatory, lymphoproliferative, and neoplastic lesions. They often present as a palpable mass in the superolateral orbit. There is significant overlap in clinical presentation, and imaging with ultrasound, computed tomography, and magnetic resonance imaging is essential for further characterisation. Key radiological features such as laterality, lobe involvement, lesion composition, margin definition, enhancement pattern, and associated bony changes can significantly narrow the differential diagnosis. This review will describe the radiological features of lacrimal gland masses to guide decision-making.